Determinants of charitable giving in Malaysia. Issue 4 (14th November 2016) - Mohd Arshad, Mohd Nahar
Abstract : Purpose: The purpose of this study is to investigate into the factors that influence charitable giving in Malaysia. Design/methodology/approach: The study employs Malaysia'sHousehold Income Survey 2009 . Results are obtained by undertaking a regression analysis. In the econometric model, charitable giving is proxied by transfer payment made by every respondent. The variable is considered as the dependent variable, while demographic, educational, occupational and geographical factors have been considered as the independent variables. Findings: In general, factors such as income, age, educational levels, marital status, gender and geographical location have statistically significant effects on Malaysians' charitable giving. A 1 per cent increase in income would result in an increase in charitable giving by 1.5 per cent, ceteris paribus . In Malaysia, charitable giving would initially increase and peaked at the age of 40 years before decline slowly over the working age – inverted-U shape of the charity–age curve. Women donate 8.7 per cent more than men. The upper secondary school has the highest marginal effects on charitable giving at 10.7 per cent. After upper secondary school, the marginal effects of subsequent levels of education on charitable giving diminish. Research limitations/implications: The findings need to be supported with experimental studies for more consistent evidence. Practical implications: Charitable giving can be nurtured especially through early years of education. Social implications: The understanding derived from this study is crucial in the efforts to build an inclusive and caring heterogeneous Malaysian society. Originality/value: This study pioneers large sample analysis to understand charitable giving behavior by Malaysians. The computation of marginal effects of education on charitable giving is another major contribution of this study.